Mid-Term Functional Outcomes Following Reoperation after Total Ankle Arthroplasty: A Case- Control Study. Issue 4 (November 2022) - Kim, Jaeyoung; Rajan, Lavan; Mizher, Rami; Srikumar, Syian; Fuller, Robert; O'Malley, Martin J.; Levine, David S.; Deland, Jonathan T.; Ellis, Scott J.; Demetracopoulos, Constantine A.
Category: Ankle Arthritis; Ankle Introduction/Purpose: A relatively frequent need for secondary surgery is an important consideration when treating end-stage ankle arthritis with total ankle arthroplasty (TAA). Despite a significant reported rate of non-revision reoperation after TAA, it is uncertain if these subsequent procedures have an impact on the longer term outcomes. It is imperative to know whether patients undergoing reoperation after TAA would have comparable functional ability compared to those with uncomplicated TAA in order to optimize patient outcomes when faced with complications after TAA. This study aimed to compare minimum five-year functional outcomes of patients who had undergone reoperation after TAA to those who did not require reoperation. Methods: Seventy-six ankles (74 patients) who underwent TAA with the Salto Talaris fixed bearing system between 2007 to 2014 were allocated into two groups based on presence (n=16) or absence of reoperation (n=60). Reoperations included all secondary procedures after index TAA, excluding revision surgeries requiring removal or exchange of the original prosthesis. The foot and ankle outcome score (FAOS) at preoperative and minimum five-year follow-up was compared between the groups. Additionally, improvements in FAOS subscales were compared. Preoperative deformity, postoperative implant alignment, number of periprosthetic cysts, and subsidence between groups were compared using standard weightbearing radiographs. A subgroup analysis was performed to compare clinical and radiographic outcomes of gutter impingement patients to those of uncomplicated group. Results: The most common cause of reoperation was gutter impingement (n=11), followed by stress fracture of the medial malleolus (n=2), tarsal tunnel syndrome (n=1), periprosthetic cyst (n=1), and infection (n=1). In comparison to the non- reoperation group, all FAOS subscales except for the Sports and Recreational Activities subscale were significantly lower in the reoperation group at final follow-up. The reoperation group exhibited significantly less improvement in the Pain, Symptoms, and Quality of Life subscales at final follow-up (p<0.05, Figure 1). There were no statistical differences in the radiographic parameters between both groups. In a subgroup analysis, all FAOS subscales at final follow-up were significantly lower in the gutter debridement patient group. There was significantly less improvement in the Pain, Symptoms, and QoL subscales in the gutter debridement patient group compared to the non-reoperation group (p<0.05 in all three subscales). Postoperative radiograph showed no differences between groups. Conclusion: Patients who underwent reoperation after TAA demonstrated inferior functional outcomes at mid-term follow-up. At the time of the primary TAA, an emphasis should be placed on carefully examining and preventing possible causes of reoperation to achieve favorable patient outcomes. Additionally, when faced with performing a reoperation following TAA, a thorough evaluation to determine the underlying cause of the reoperation should be performed to guide treatment.